Attenuated serotonin transporter association between dorsal raphe and ventral striatum in major depression. Issue 8 (17th January 2014) - Hahn, Andreas; Haeusler, Daniela; Kraus, Christoph; Höflich, Anna S.; Kranz, Georg S.; Baldinger, Pia; Savli, Markus; Mitterhauser, Markus; Wadsak, Wolfgang; Karanikas, Georgios; Kasper, Siegfried; Lanzenberger, Rupert
Abstract Suffering from anhedonia, patients with major depressive disorder (MDD) exhibit alterations in several parts of the serotonergic neurotransmitter system, which are in turn involved in reward processing. However, previous investigations of the serotonin transporter (SERT) focused on regional differences with varying results depending on the clinical syndrome. Here, we aimed to describe the serotonergic system of MDD patients on a network level by evaluating SERT associations across brain regions. Twenty medication free patients with major depression and 20 healthy controls underwent positron emission tomography using the radioligand [11C]DASB. SERT binding potentials (BPND) were quantified voxel‐wise with the multilinear reference tissue model 2. In addition, SERT BPND was extracted from the dorsal raphe nucleus (DRN) as an indicator of midbrain serotonergic neurotransmission. Whole‐brain linear regression analysis was applied to evaluate the association of DRN SERT bindings to those in projection areas, which was followed by ANCOVA to assess differences in interregional relationships between patients and controls. Although both groups showed widespread positive correlations, group differences were restricted to decreased SERT associations between the DRN and the ventral striatum (right and left respectively: t = 5.85, P < 0.05 corrected and t = 5.07, P < 0.1 corrected) when comparing MDD patients (R2 = 0.11 and 0.24) to healthy subjects (R2 = 0.72 and 0.66, P < 0.01 and 0.05 corrected). Adjusting for age and sex did not change these findings. This study indicates a disturbed regulation between key regions involved in reward processing via the SERT. Our interregional approach highlights the importance of evaluating pathophysiological alterations on a network level to gain complementary information in addition to regional investigations. Hum Brain Mapp 35:3857–3866, 2014. © 2014 Wiley Periodicals, Inc.